Maximum likelihood estimation and inference : with examples in R, SAS, and ADMB - Millar, R. B. (Russell B.) (Chichester, West Sussex : Wiley, 2011)
'Applied Likelihood Methods provides an accessible and practical introduction to likelihood modeling, supported by examples and software. The book features applications from a range of disciplines, including statistics, medicine, biology, and ecology. The methods are implemented in SAS--the most widely used statistical software package--and the data sets and SAS code are provided on a Web site, enabling the reader to use the methods to solve problems in their own work. This book serves as an ideal text for applied scientists and researchers and graduate students of statistics'--
'This book is the first to provide an accessible and practical introduction to likelihood modeling, supported by examples and software, and is suitable for the applied scientist'--
Includes bibliographical references and index.
Keywords: Estimation theory; Chance -- Mathematical models